Industries and enterprises of North Korea: Facts, concepts, and trends - Seogki Lee; Suk Lee (Korea Development Institute (KDI), 2022)
In the study of the North Korean economy, industrial and business activities still remain uncharted territory. They are the most basic components of an economy, yet the scarcity of information makes those in North Korea almost impossible to understand from the outside world. Today, the general perception is that North Korea's industrial and business activities have completely changed from those of past socialist economies. In fact, rather than central plans, capitalist factors such as markets and profit are becoming the daily standards, and North Korea's industry and business activities are by no means exceptions to these so-called changes and economic reforms. To understand the present status and future direction of the North Korean economy, it is important to grasp how industry is managed and business activities are conducted.
Keywords: 330; Industrie; Unternehmen; Industrialisierung; Wirtschaftsgeschichte; Nordkorea